Environmental contamination with feces of free-roaming dogs and the risk of transmission of Echinococcus and Taenia species in urban regions of southeastern Iran - Shamsaddini, Saeedeh; Schneider, Carina; Dumendiak, Sonja; Aghassi, Hossein; Kamyabi, Hossein; Akhlaghi, Elham; Wassermann, Marion; Fasihi Harandi, Majid; Deplazes, Peter; Romig, Thomas (Parasites & vectors, 2024)
Background Dogs are the most important definitive hosts of zoonotic taeniid helminths worldwide. Different Echinococcus and Taenia species of domestic and wild carnivores pose a potential risk to human population. High populations of free-roaming dogs (FRDs) in urban areas of Iran and widespread contamination of the environment with dog feces is a potential source of infecting people living in the urban regions with cystic echinococcosis (CE). Our knowledge on the risk of CE transmission in the urban settings in the endemic regions is limited. The present study surveyed the species and genotypes of E. granulosus sensu lato and other taeniids by examining feces of free-roaming dogs in the urban areas in the city of Kerman, southeastern Iran. Methods The city was divided into 100 consecutive blocks of which 25 blocks were randomly selected. Fecal samples of FRDs were counted, mapped and fresh samples were collected. Then Zinc chloride flotation, and sequential sieving was performed, and the samples were examined under an inverted microscope. Single individual taeniid eggs were isolated, partial nad1 gene was amplified and sequenced to identify species and genotypes. Results In total 5607 fecal samples of dogs were mapped and 83 fresh samples were collected. Taeniid eggs were detected in nine fecal samples (10.8%) from seven out of the 25 city blocks (28.0%). Echinococcus eggs were found in four samples (4.8%) from three city blocks, two samples containing E. granulosus sensu stricto (2.4%), two samples containing E. canadensis G6/7 (2.4%). In addition, three samples contained eggs of Taenia hydatigena (3.6%), and one sample of Taenia serialis (1.2%). Conclusions This study documented the potential risk of CE transmission to humans resulting from the feces of dogs roaming freely in urban areas. Graphical Abstract